2012
DOI: 10.1248/cpb.c12-00290
|View full text |Cite
|
Sign up to set email alerts
|

Polycationic Gramicidin S Analogues with Both High Antibiotic Activity and Very Low Hemolytic Activity

Abstract: and Pro 5,5′ residues whose modification will significantly increase the therapeutic index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
0
13
0
3
Order By: Relevance
“…Previous studies have shown that self-assembling nanoantibiotics effectively localize antibiotics to the periplasmic space, thus allowing them to exert their bacterial activities against gram-negative bacteria. 9,10,29 In an attempt to augment and hone this strategy, biodegradable hydrophobic copolymers of PLGA have been attached to the N-termini of BA to design a novel class of selfassembling nano-BAs. Compared with other compounds, such as fatty acids, PLGA has attracted considerable attention for its attractive characteristics: 1) biodegradability and biocompatibility, 2) US Food and Drug Administration and European Medicine Agency approval in drug delivery systems for parenteral administration, 3) well-described formulations and methods of production adapted to various types of drugs (eg, hydrophilic or hydrophobic small molecules or macromolecules), 4) ability to modify surface properties to provide stealth and/or better interaction with biological materials, and 5) ability to target nanoparticles to specific organs or cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that self-assembling nanoantibiotics effectively localize antibiotics to the periplasmic space, thus allowing them to exert their bacterial activities against gram-negative bacteria. 9,10,29 In an attempt to augment and hone this strategy, biodegradable hydrophobic copolymers of PLGA have been attached to the N-termini of BA to design a novel class of selfassembling nano-BAs. Compared with other compounds, such as fatty acids, PLGA has attracted considerable attention for its attractive characteristics: 1) biodegradability and biocompatibility, 2) US Food and Drug Administration and European Medicine Agency approval in drug delivery systems for parenteral administration, 3) well-described formulations and methods of production adapted to various types of drugs (eg, hydrophilic or hydrophobic small molecules or macromolecules), 4) ability to modify surface properties to provide stealth and/or better interaction with biological materials, and 5) ability to target nanoparticles to specific organs or cells.…”
Section: Discussionmentioning
confidence: 99%
“…The latter one (due to its positive charges) is potentially capable of cooperatively coupling in an aqueous solution with negatively charged membrane of a microbial cell. Such powerful multipoint electrostatic interaction is actively used in modern polycationic antiseptics [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have shown that seemingly subtle changes in the β-turn region could have a dramatic impact on the antimicrobial activity, suggesting that this region may be a hot spot for modulating GS structure and activity. Interestingly, the effect of these modifications on the antimicrobial activity is often not correlated with the cytotoxicity. , Two general methods have been adopted for β-turn region modifications: one involves the modification of D Phe and/or Pro residues, while the other involves replacement of the entire D Phe-Pro sequence with dipeptide surrogates.…”
Section: Structure–activity Relationship Of Gramicidin S and Its Anal...mentioning
confidence: 99%
“…Investigations of GS analogues with a modified β-turn region have indicated that the hydrophobic aromaticity is critical for maintaining the antimicrobial activity, , with only a few exceptions . Impressively, extra amino groups on Pro often resulted in decreased hemolytic activity while largely maintaining the antimicrobial activity, leading to a popular modification strategy .…”
Section: Structure–activity Relationship Of Gramicidin S and Its Anal...mentioning
confidence: 99%